1982
DOI: 10.1002/fedr.19820930103
|View full text |Cite
|
Sign up to set email alerts
|

Karyology and hydridization in the Carex flava complex in Switzerland

Abstract: The karyology of Carex flava aggregate in Switzerland was investigated. Fertility was measured and crossings were done. The microsporogenesis is described. In Switzerland, the C. flava group consists of C. flava var. flava (n = 30, 31), C. flava var. alpina (n = 30, 31), C. lepidocarpa (n = 34), C. demissa (n = 34, 35), and C. serotina (n = 34, 35, 36). The three species with high chromosome numbers often grow together with C. flava. Accordingly, F1‐hybrids with this parental species are frequent. Their meiosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 13 publications
(1 reference statement)
5
55
0
Order By: Relevance
“…Heilborn also hypothesized that the direction of evolutionary change in the genus has been from lower to higher chromosome numbers (Heilborn, 1924: 188), and subsequent researchers (Davies, 1956;Hoshino, 1981;Schmid, 1982;Luceño & Castroviejo, 1993) have assumed this hypothesis to be true. Heilborn's hypothesis implies that ancestral character state reconstructions should recover lower numbers at the deepest nodes of a phylogeny.…”
Section: Systematic Distribution Of Chromosome Numbersmentioning
confidence: 94%
See 2 more Smart Citations
“…Heilborn also hypothesized that the direction of evolutionary change in the genus has been from lower to higher chromosome numbers (Heilborn, 1924: 188), and subsequent researchers (Davies, 1956;Hoshino, 1981;Schmid, 1982;Luceño & Castroviejo, 1993) have assumed this hypothesis to be true. Heilborn's hypothesis implies that ancestral character state reconstructions should recover lower numbers at the deepest nodes of a phylogeny.…”
Section: Systematic Distribution Of Chromosome Numbersmentioning
confidence: 94%
“…Agmatoploidy contrasts with strict or quantitative aneuploidy, which refers to chromosome number changes due to duplication of single chromosomes; polyploidy, which refers to duplications of whole sets of chromosomes; and dysploidy, which is a general term for chromosome number changes by any mechanism that involve only a subset of an organism's chromosomes (Löve et al, 1957). Heilborn (1924: 210) held that although chromosome fission probably played a role in the origins of Carex, more recent chromosome number increases in the genus must be a consequence of chromosome duplications (also see Tanaka, 1949;Schmid, 1982). Tanaka (1949: 23) reported that in 44 plants from 21 different species, the pattern "(n-2) II+1III+1I" is predominant, which he suggested was evidence of quantitative aneuploidy (either one duplication and one deletion or two duplications).…”
Section: Mode Of Chromosome Evolution In Carex: Agmatoploidy Aneuplomentioning
confidence: 98%
See 1 more Smart Citation
“…Carex is the largest and most diverse group of organisms exhibiting holocentric chromosomes and agmatoploid evo- lution (Reznicek 1990) with polymorphisms between closely related species, as well as within species (Faulkner 1972;Schmid 1982;Whitkus 1991;Hoshino and Okamura 1994;Hoshino and Onimatsu 1994). Monoecy in the genus allows for artificial crosses to be made with relative ease, and plants are easily cloned.…”
Section: Questionsmentioning
confidence: 99%
“…Furthermore, hybrids between plants with different numbers of chromosomes reveal one large chromosome pairing with two small chromosomes (Wahl 1940;Tanaka 1949;Håkansson 1954;Davies 1955;Faulkner 1972;Schmid 1982;Cayouette andMorisset 1985, 1986;Hoshino et al 1993Hoshino et al , 1994Hoshino and Okamura 1994). Complicating the picture in hybrids from natural populations is the presence of various univalent and multivalent formations suggesting chromosomal structural rearrangements are involved (Tanaka 1949;Faulkner 1973;Schmid 1982;Cayouette and Morissett 1986;Hoshino and Waterway 1994).…”
Section: Introductionmentioning
confidence: 99%